Effect of mulching on yield of ginger (Zingiber officinale Rosc.) - Govind, Ram Chandra, Sheo (Journal of Spices and Aromatic Crops, 2001)
Field experiments were conducted at Barapani, Meghalaya to evaluate the response of ginger to the application of locally available organic mulches. Five treatments namely, paddy straw mulch, Schima wallichii dry leaf mulch, Eupatorium odoratum green stem and leaf mulch, Pinus kesia dry leaf mulch and unmulched control were compared in the present study. Use of organic mulches enhanced the sprouting, reduced the dry matter accumulation by weeds and improved the growth and yield of ginger significantly. Paddy straw and Schima leaves were superior as these mulches increased the yield by 43.6% and 39.7% over control, respectively.